Gallbladder perforation with concomitant liver abscess: a case report with a review of treatment options - Quiroga Garza, Alejandro; Muñoz Leija, Milton Alberto; Valdivia Balderas, Juan Manuel; Guzmán López, Santos; Elizondo Omaña, Rodrigo E. (International Surgery Journal, 2020)
Gallbladder perforation (GBP) management is still controversial in regards to time (early vs. interval), first procedure (surgical vs. drainage) and technique (laparoscopic vs. open). This is the case report of an adult patient with GBP Niemeier type II, complicated with a concomitant hepatic abscess. The patient was treated medically and with laparoscopic drainage of abscess and pyocholecistolithiasis. She was scheduled shortly after for endoscopic retrograde cholangiopancreatography, and posteriorly for definitive treatment with laparoscopic cholecystectomy 1 month later. Satisfactory postsurgical outcome, with uneventful 1-month follow-up.